Peterson's four-year colleges 2007 (Thomson Peterson's, 2006)
Four Year Colleges - 2007 Edition" (2,922 pages--it should be sold "by the pound"!) is essentialy 2 books in 1. The first 1000 pages of the book present a summary of about 2,200 colleges around the US. On the average, all colleges get about half a page description. The second part of the book is a more in-depth (two pages) profile of about 1,000 colleges. It is important to understand that those in-depth profiles are NOT written up by the book's editors, but instead by the colleges themselves (and the colleges have paid for this placement).